FRI0038 Pharmacodynamic Effect of Intravenous Golimumab by Messenger RNA Expression Profiling. (10th June 2014) - Cherkas, Y.; Brodmerkel, C.; Curran, M.; Lamberth, S.
Abstract : Background: Rheumatoid Arthritis (RA) is a chronic systemic autoimmune disease resulting in joint inflammation and damage. Despite the current therapies available, only a small percentage of RA pts achieve remission. To improve care and treatment for RA pts, a deeper understanding of the mechanisms that drive disease and response to therapy are desirable. The molecular understanding of disease and treatment mechanisms of RA continues to evolve. Objectives: To explore the utility of peripheral blood expression profiling for informing disease and treatment mechanisms, samples derived from the GO-FURTHER golimumab study in RA were evaluated. This study examines if whole blood (WB) gene expression profiles can be utilized to: identify a baseline disease profile (DP) for pts with moderate-to-severe RA elucidate the pharmacodynamic (PD) and response profile of golimumab IV treatment, and delineate the peripheral biological processes dysregulated in RA and modulated by golimumab IV. Methods: mRNA from 487 WB samples collected in a Phase III study of golimumab IV (GO-FURTHER) in pts with active RA despite methotrexate (MTX) therapy was isolated and profiled using the Affymetrix HT HG-U133+ PM Array (Santa Clara, CA). Samples were collected at Wks 0 and 14 from pts treated with IV placebo + MTX (PBO; n=161) or IV golimumab 2mg/kg + MTX (GLM; n=326) administered at Wks 0, 4, and every 8 wks thereafter. Non-RA WB samples (healthy controls; n=22) were obtained from Bioreclamation (Hicksville, NY). Results: A disease profile comparing baseline gene expression profiles of RA to healthy controls yielded about 2000 differentially expressed genes (DEGs), while comparison of post-treatment to pre-treatment samples generated a PD profile of about 3000 DEGs. Over 70% of genes in the DP are downregulated as well as humoral immune response and B and T cell receptor signaling pathways. Pathways upregulated in the DP include innate immune response, Toll-like receptor (TLR), and cell activation. Treatment with golimumab modulates more than 30% of the disease profile, while just over 25% of PD effect is shared with the DP. The above mentioned pathways are common between the DP and PD profiles and are reversed, in part, through changes in peripheral cell populations post-golimumab treatment. A significant decrease in neutrophils and increase in lymphocytes was observed in the periphery at Wk 12 and in gene expression profiles representative of these cells at Wk 14 post-treatment. In addition, response to golimumab at Wk 14 was associated with more gene changes in B and T cell receptor signaling pathways in comparison to nonresponders. Conclusions: Gene expression from the periphery of RA pts can be used for identification of a DP as well as the PD effect and response profile to golimumab IV. The most significant biological pathways and functions associated with the DP or PD effect are related to immune response and function. At baseline, RA pts had an increased innate and decreased adaptive immune profile in the periphery and majority of these processes were reversed by treatment with golimumab IV. Defining the pathways dysregulated in RA and modified by effective treatment as well as those that remain dysregulated aids in defining novel areas for potential therapeutic intervention. Disclosure of Interest: Y. Cherkas Employee of: Janssen Research & Development, LLC., C. Brodmerkel Employee of: Janssen Research & Development, LLC., M. Curran Employee of: Janssen Research & Development, LLC., S. Lamberth Employee of: Janssen Research & Development, LLC. DOI: 10.1136/annrheumdis-2014-eular.2032